Análisis Financiero a la Cooperativa de Ahorro y Crédito de la Pequeña Empresa “CACPE Loja Ltda.” de la ciudad de Loja, periodos 2020-2021. - Quezada Morocho, Teresa Valeria (2023)
The Curricular Integration Work called: Financial Analysis of the Small Business Savings and Credit Cooperative "CACPE Loja Ltda." of the city of Loja, periods 2020-2021, was carried out to comply with the objectives set. The work was developed with a qualitative- quantitative approach, the design is descriptive because it characterizes the economic- financial status of the entity through observation and analysis, several methods and techniques were used which allowed the collection of information facilitating the interpretation of financial data. The vertical analysis was performed, which allowed determining the participation of each of the accounts of the statement of financial position and income statements, where it was obtained that in the periods 2020-2021 the most significant account of the Assets is the Loan Portfolio with 76.71% and 75.54% respectively, in this case it shows that its institutional mission, which is the financial intermediation, is fulfilled in terms of credit services provided; In the Liabilities, the most representative account is the Obligations with the Public, reflecting percentages of 68.75% and 74.48%, with term deposits being the subaccount with the highest representation, thus guaranteeing the members the opportunity to invest their resources safely and with convenient interest; the Equity is mainly constituted by the Reserves with 12.34% and 11.92%, which come from the liquid operating profits or surpluses of the fiscal year. On the other hand, in the economic structure, Expenses are mainly made up of Operating Expenses which in the year 2020 presents 45.29% and in the year 2021 39.18% values recorded for labor relationship and Profit which constitutes 4.56% and 10.79% due to the fact that income has been greater than expenses in both periods. Similarly, the horizontal analysis was applied to compare the accounts, qualifying the management of one period with respect to the other, showing the increases and decreases, the Assets reached an increase of 11.19% for the second year, the Liabilities and Equity increased by 11.71% and 9.01%, the accounts with the greatest variation being Accounts Payable and Profit and Loss. With respect to the income statement, in Expenses there was an increase for the year 2021 due to interest incurred and other expenses and losses, in Income there was a growth of 15.02% generated by the development of the activities, which is favorable because it allows to increase the benefits and ensure its profitability within the financial market, as for the Profit it increased 172.16% in view that in the year 2021 it generated higher income. With the application of the financial indicators established by the Superintendence of Popular and Solidarity Economy of segment 1, it was possible to measure the behavior and financial performance, in terms of Equity Sufficiency 5 increased to the year 2021 by 44.32% showing a good economic-financial position, due to the fact that the equity exceeded the total of immobilized assets, the Portfolio Delinquency has increased by 1, Liquidity maintains a percentage of 59.75%, which satisfies the immediate cash requirements of its depositors, and in the Vulnerability of the Equity there was a variation of 4.47%, which indicates that the entity can solve the non-performing loan portfolio in the face of any risk. Finally, a financial analysis report was prepared containing the general results obtained, as well as the conclusions and recommendations appropriate to the entity's situation, which will allow the directors to make the right decisions focused on improving the development of the cooperative's activities.